2015
DOI: 10.18202/jamal.2015.12.6027
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian Hospitals under the “BPJS” Scheme: a War in a Narrower Battlefield

Abstract: Abstrak: Rumah Sakit Indonesia di Bawah Skema "BPJS": SebuahPeperangan di Medan Sempit. Studi kualitatif ini mencoba menjawab implikasi tekanan biaya dan kualitas yang disebabkan adanya skema BPJS di rumah sakit. Studi ini menggunakan observasi serta wawancara pada personel kunci di bagian keuangan dari lima rumah sakit yang berlokasi di Malang, Blitar, dan Tulung Agung. Dengan mengikuti tradisi interpretivisme, teori institusionalisasi digunakan untuk analisis data. Ditemukan bahwa perubahan transformasional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
3
0
3
Order By: Relevance
“…17 This condition threatens the financial sustainability of Indonesian hospitals which were struggling to adjust to the changes in the new payment system. 16 In fact, for American hospitals that have long adapted to payment reforms, the crisis has still created financial challenges. 6 Nonetheless, the study results revealed that the leading cause of the decrease inpatient visits was due to patient fear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 This condition threatens the financial sustainability of Indonesian hospitals which were struggling to adjust to the changes in the new payment system. 16 In fact, for American hospitals that have long adapted to payment reforms, the crisis has still created financial challenges. 6 Nonetheless, the study results revealed that the leading cause of the decrease inpatient visits was due to patient fear.…”
Section: Discussionmentioning
confidence: 99%
“…15 Before the COVID-19 pandemic hit, hospitals in Indonesia were undergoing a major change in implementing a new health insurance system, the National Health Insurance as an effort to achieve Universal Health Coverage. Due to standardized rates and quality of the new insurance system, the hospitals that previously only focused on providing services, 16 had to carefully calculate the costs because they could no longer compensate service fees incurred on service rates. Unfortunately, the COVID-19 pandemic hit Indonesia just as hospitals in Indonesia began to adjust.…”
mentioning
confidence: 99%
“…Riset lainnya menghasilkan temuan bahwa penyusunan framework rantai nilai kelompok usaha jasa telematika mendapat penekanan sebagai langkah untuk menyu sun strategi peningkatan daya saing (Tosida, Thaheer, & Maryana, 2015). Lebih jauh lagi, riset Queensland Public Sector menegaskan alasan/manfaat pengembangan mo del nilai yakni meningkatkan harapan klien, pe mangku kepentingan, dan masyarakat bah wa akses ke layanan publik akan mulus dan tidak membingungkan, meningkatkan nilai publik, dan meningkatkan kebutuhan untuk penyelarasan (sinergi) dalam rangka mening katkan efektivitas dan efisiensi layanan pub lik (Djamhuri & Amirya, 2015).…”
Section: Hasil Dan Pembahasanunclassified
“…Tarif kapitasi dan Case Base Group (CBG) yang ditetapkan Kemen terian Kesehatan (Kemenkes) masih jauh dari harga keekonomian untuk kualitas yang diharapkan. Djamhuri & Amirya (2015) dan Kartini (2018) menemukan bahwa BPJS Ke sehatan memang merepresentasikan "kua sa" kepada rumah sakit. Kuasa tersebut dipraktikkan mengimplementasikan ukur anukuran yang lebih ketat dalam hal biaya ataupun kualitas (Fiondella et al, 2016;Sari et al, 2015).…”
unclassified
“…Oppi et al, 2019). Pada sisi lainnya, RS swasta menghadapi ma salah JKN yang intinya terkait dengan tarif yang berhubungan dengan kecukupan pem biayaan(Djamhuri & Amirya, 2015). Harap an RS swasta belum terakomodasi pada Ta rif INACBGs saat ini.…”
unclassified